Clinical significance of miR-200a in systemic lupus erythematosus and renal damage in children: miR-200a and SLE and renal damage in children - Zhang, Haiyan; Zhou, Xiaoqing; Li, Qinghu; Zheng, Min (Cellular and Molecular Biology, 2024)
The purpose was to analyze the clinical significance of miR-200a in children with initially diagnosed SLE and renal damage. Children with initially diagnosed SLE (n=100) and healthy children (n=50) undergoing physical examinations during the same period were recruited. Disease activity of SLE children was determined based on SLEDAI (systemic lupus erythematosus disease activity index), and they were divided to SLEDAI≤9 group and SLEDAI>9 group, respectively. Moreover, SLE children were divided to LN group and non-LN group based on the occurrence of lupus nephritis. Differential level of miR-200a between groups was detected by qRT-PCR. Spearman correlation test was conducted to analyze the influence of miR-200a on SLEDAI and other laboratory indexes of SLE children. Its diagnostic potential in SLE and LN was assessed through depicting ROC curves. MiR-200a level was remarkably lower in SLE children than that of healthy children. Lower level of miR-200a was detected in SLE children with high SLEDAI or accompanied LN. MiR-200a level was negatively correlated to SLEDAI (r=-0.425), ESR (r=-0.284), CRP (r=-0.338), BUN (r=-0.263) and Scr (r=-0.345), while it was positively correlated to C3 (r=0.631), C4 (r=0.524) and ALB (r=0.394) in SLE children. The AUC of miR-200a in diagnosing SLE was 0.8379 (cut-off value=2.225, sensitivity=70%, specificity=70%). Besides, the AUC of miR-200a in diagnosing LN was 0.7619 (cut-off value=2.005, sensitivity=80%, specificity=76%). MiR-200a level has a certain correlation to the disease activity of children with initially diagnosed SLE, which can be utilized as an adjuvant indicator in evaluating SLE severity. Meanwhile, miR-200a has predictive value for SLE-induced renal damage.